Many-body effects for excitonic high-order wave mixing in monolayer transition metal dichalcogenides - H. K. Avetissian; G. F. Mkrtchian; K. Z. Hatsagortsyan (Physical Review Research, 2020)
A microscopic quantum theory describing the nonlinear and nonperturbative optical response of monolayer transition metal dichalcogenides (MTMDs) to a two-color strong laser field is developed within the dynamical Hartree-Fock approximation. Taking into account the recently recognized importance of MTMD two-dimensional nanostructures for light-wave electronics and optical communication, we investigate the influence of many-body effects in the nonlinear optical response. The high-frequency component of the field resonantly generates tightly bound excitons, and the low-frequency strong field component induces excitonic high-order wave mixing/harmonic generation (HWM/HHG). The considerable enhancement of HWM/HHG spectra due to many-body excitonic effects is observed, which modifies the relative contribution of the interband and intraband channels, and essentially reshapes the radiation spectra. Our analysis confirms the efficiency of HWM and HHG in MTMDs, which may provide a promising platform for ultrafast modulation of light for optical communication.